Metal soft magnetic composite material and preparation method and application thereof

By sequentially covering the aluminum nitride layer and the silicone resin layer on the surface of the metal soft magnetic powder, the problems of large losses and insufficient heat resistance and heat dissipation performance in the prior art are solved, and the effects of high frequency and low loss and good heat resistance and heat dissipation performance are achieved.

CN119920559APending Publication Date: 2025-05-02HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311449355.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing metal soft magnetic composite materials have large losses under high-frequency conditions and insufficient heat resistance and heat dissipation performance, resulting in poor overheating and poor performance of electronic devices in high-frequency scenarios.

Method used

The metal soft magnetic powder is coated successively with an aluminum nitride layer and a silicone resin layer, and the bonding force is enhanced by combining a silane coupling agent to form a multi-layer insulating coating structure.

Benefits of technology

It effectively reduces the loss of metal soft magnetic composite materials, improves its resistivity and heat dissipation performance at high frequencies, and meets the application requirements under high frequencies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920559A_ABST
    Figure CN119920559A_ABST
Patent Text Reader

Abstract

The invention provides a metal soft magnetic composite material and a preparation method and application thereof. The metal soft magnetic composite material comprises metal soft magnetic powder, an aluminum nitride layer and an organic silicon resin layer, wherein the aluminum nitride layer and the organic silicon resin layer sequentially cover the outer surface of the metal soft magnetic powder. The weight of the aluminum nitride layer is 1-5wt% of the weight of the metal soft magnetic powder; and the weight of the organic silicon resin layer is 0.8-4 wt% of the weight of the metal soft magnetic powder. The metal soft magnetic composite material with high frequency, low loss and good heat resistance and heat dissipation performance can be obtained at low cost through a simple operation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soft magnetic materials, and in particular to a metal soft magnetic composite material and a preparation method and application thereof. Background Art

[0002] Metal soft magnetic composite materials have the characteristics of high saturation flux density and wide operating frequency range and are widely used in photovoltaic power generation, variable frequency air conditioners, new energy vehicles and charging piles, data centers, energy storage, consumer electronics and other fields. Metal soft magnetic composite materials are usually composed of soft magnetic particles with an insulating coating structure. Among them, the insulating coating has a key influence on the saturation magnetization intensity, coercive force and resistivity of the metal soft magnetic composite materials. At present, high resistivity, uniform insulating coating layers such as phosphate / silicone resin composite coating layers, SiO2 / epoxy resin composite coating layers, etc. have been studied by many scholars and achieved the goal of high resistance and low loss. However, in the face of the development trend of electronic devices being light, thin and miniaturized, integrated and intelligent, and the working environment of high current and high frequency, not only are metal soft magnetic composite materials required to have low loss performance at high frequencies, but also high requirements are placed on their temperature stability and heat dissipation capabilities.

[0003] The phosphating layer in the currently commonly used phosphate insulation coating technology will decompose at 550°C, causing the insulation layer to be destroyed and the loss to increase significantly under high frequency; inorganic oxides such as SiO2, Al2O3 and MgO have low thermal conductivity as insulation layers and cannot effectively dissipate heat, which leads to problems such as overheating of electronic devices under high frequency conditions; in addition, the binders used in metal soft magnetic composite materials, such as epoxy resins and silicone resins, are not resistant to high temperatures and will decompose during subsequent heat treatment, thereby reducing the stability and bonding strength of the insulation layer.

[0004] Therefore, it is of great significance to develop a metal soft magnetic composite material that has both high-frequency and low-loss performance and high-temperature stability to solve the application problems of electronic devices in high-frequency scenarios.

[0005] In the prior art, CN 113724957 A discloses a method for preparing a soft magnetic composite powder for a molded inductor with high DC bias and fast heat dissipation, and a soft magnetic powder core. The method adopts magnesium oxide as an insulating coating layer and an organic binder as a multilayer coating structure of an organic coating layer, which effectively reduces the loss, improves the DC bias characteristics, oxidation resistance and corrosion resistance, and improves the heat dissipation performance of the magnetic core to a certain extent. However, the thermal conductivity of magnesium oxide at room temperature is relatively high, and the heat dissipation effect is limited. CN114512323 A discloses a method for preparing a MnO-SiO2 insulating coated metal soft magnetic powder core, which first adds a silane coupling agent to the MnO2 powder, then mixes it with the metal powder, dries it, granulates it, and presses it into a green body, and then heats the green body to obtain a MnO-SiO2 insulating coated metal soft magnetic powder core. The method effectively solves the problem that the phosphoric acid passivation layer is easy to decompose at high temperature. However, the magnetic permeability of the soft magnetic powder core prepared by this method is low and the loss is high, which makes it difficult to meet the performance requirements of high-frequency applications.

[0006] In summary, the existing technology has the following problems: the process is complicated, the cost is high, the magnetic loss of the product is high, and the heat resistance and heat dissipation performance still cannot meet the application requirements of the magnetic core under high frequency conditions. Summary of the invention

[0007] The main purpose of the present invention is to provide a metal soft magnetic composite material and its preparation method and application, so as to solve the following problems existing in the preparation process of metal soft magnetic composite materials in the prior art: complex process flow, high cost, high magnetic loss of the product, and heat resistance and heat dissipation performance still cannot meet the application requirements of the magnetic core under high frequency conditions.

[0008] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a metal soft magnetic composite material is provided, which includes a metal soft magnetic powder and an aluminum nitride layer and a silicone resin layer sequentially coated on the outer surface of the metal soft magnetic powder; the weight of the aluminum nitride layer is 1 to 5wt% of the weight of the metal soft magnetic powder; the weight of the silicone resin layer is 0.8 to 4wt% of the weight of the metal soft magnetic powder.

[0009] Furthermore, the aluminum nitride layer and the silicone resin layer are bonded by a silane coupling agent; preferably, the silane coupling agent is selected from one or more of vinyl silane, alkyl silane or amino silane; further preferably, the vinyl silane is selected from one or more of KH-151, KH-171, KH-172 or KH-188; further preferably, the alkyl silane is selected from one or more of KH-2421, KH-481, KH-681 or KH-330; further preferably, the amino silane is selected from one or more of KH-550, KH-902, KH-602 or KH-703.

[0010] Further, the metal soft magnetic powder is one or more of iron silicon powder, sendustine powder or iron nickel molybdenum powder; further preferably, the composition of the iron silicon powder includes 94.4-95.4wt% of Fe, 4.5-5.5wt% of Si and the remainder of inevitable impurities by weight; further preferably, the composition of the sendustine powder includes 84.1-85.7wt% of Fe, 9-10wt% of Si, 5.2-5.8wt% of Al and the remainder of inevitable impurities by weight; further preferably, the composition of the iron nickel molybdenum powder includes 17.8-19.9wt% of Fe, 1.5-2.5wt% of Mo, 78.5-79.6wt% of Ni and the remainder of inevitable impurities by weight.

[0011] Furthermore, the material of the organic silicone resin layer is methylphenyl silicone resin; preferably, the methylphenyl silicone resin is selected from one or more of KR-272, KR-311 or KR-282.

[0012] Furthermore, the weight of the silane coupling agent is 0.5-2 wt % of the weight of the metal soft magnetic powder.

[0013] According to another aspect of the present invention, there is provided a method for preparing a metal soft magnetic composite material, comprising the following steps: step S1, mixing a metal soft magnetic powder and an aluminum nitride powder and then ball milling them to coat the outer surface of the metal soft magnetic powder with an aluminum nitride layer; step S2, mixing the metal soft magnetic powder coated with the aluminum nitride layer and a silicone resin and then granulating them to coat the outer surface of the aluminum nitride layer with a silicone resin layer.

[0014] Further, step S1 includes: S11, mixing anhydrous ethanol and metal soft magnetic powder, and then performing a first ball milling and a first drying in sequence to obtain pretreated metal soft magnetic powder; S12, mixing the pretreated metal soft magnetic powder, aluminum nitride powder and anhydrous ethanol, and then performing a second ball milling and a second drying in sequence to coat the outer surface of the metal soft magnetic powder with an aluminum nitride layer; preferably, the particle size of the metal soft magnetic powder is 200-800 mesh; preferably, the particle size of the aluminum nitride powder is 500-1000 mesh; preferably, the processing time of the first ball milling is 2-4h, and the ball-to-material ratio is 10-20:1; preferably, the processing time of the second ball milling is 12-48h, and the ball-to-material ratio is 10-20:1.

[0015] Furthermore, step S2 includes: S21, dissolving the silane coupling agent in anhydrous ethanol, and then adding the metal soft magnetic powder coated with an aluminum nitride layer into the system, and sequentially performing a first ultrasonic treatment and a third drying to obtain a surface-treated metal soft magnetic powder; S22, dissolving the silicone resin in acetone, and then adding the surface-treated metal soft magnetic powder into the system, and sequentially performing a second ultrasonic treatment, granulation, and drying to obtain a metal soft magnetic composite material.

[0016] According to another aspect of the present invention, a magnetic powder core is provided. The magnetic powder core comprises the aforementioned metal soft magnetic composite material and a release agent.

[0017] According to another aspect of the present invention, there is provided an application of the aforementioned metal soft magnetic composite material in high-frequency electronic appliances.

[0018] The present invention can obtain a metal soft magnetic composite material having high frequency, low loss and good heat resistance and heat dissipation performance at a relatively low cost through a simple operation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 The loss test diagrams of Comparative Example 1 and Example 1 of the present invention at different frequencies are shown. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0022] As described in the background technology section of this application, the prior art has the following problems: the process is complex, the cost is high, the magnetic loss of the product is high, and the heat resistance and heat dissipation performance still cannot meet the application requirements of the magnetic core under high frequency conditions. In order to solve this problem, the present application provides a metal soft magnetic composite material, which includes a metal soft magnetic powder and an aluminum nitride layer and an organic silicone resin layer sequentially coated on the outer surface of the metal soft magnetic powder; the weight of the aluminum nitride layer is 1-5wt% of the weight of the metal soft magnetic powder; the weight of the organic silicone resin layer is 0.8-4wt% of the weight of the metal soft magnetic powder.

[0023] Firstly, the setting of the aluminum nitride layer and the silicone resin layer is equivalent to sequentially setting an inorganic insulating coating layer and an organic insulating coating layer on the outer surface of the metal soft magnetic powder. Such a multi-layer insulating coating layer setting method can improve the coverage of the coating layer and effectively improve the resistivity of the metal soft magnetic composite material, thereby reducing the eddy current loss between the metal soft magnetic powders. When it is subsequently applied to high-frequency electronic appliances, the device can maintain lower power loss under high-frequency conditions.

[0024] Secondly, compared with other inorganic insulating coatings, the aluminum nitride layer as an inorganic insulating coating can not only further improve the resistivity of the metal soft magnetic composite material, but more importantly, it can also greatly improve the temperature resistance and heat dissipation of the material, so that the magnetic core can better meet the application requirements under high-frequency conditions.

[0025] Third, compared with other organic insulating coatings, the silicone resin layer, as an organic insulating coating, plays both an insulating coating and a bonding role. It can not only further improve the resistivity of the metal soft magnetic composite material, but more importantly, it also makes the material have excellent high temperature resistance and bonding properties. In the subsequent process of preparing magnetic powder core green billets from metal soft magnetic composite materials, on the one hand, it can make the billet molding performance better, and on the other hand, it can also adapt to higher heat treatment temperatures, thereby effectively releasing internal stress and further reducing hysteresis losses.

[0026] Fourthly, the cost of the above raw materials is relatively low, and the above metal soft magnetic composite material can be obtained by subsequent simple coating, and the requirements for the preparation process are also relatively low.

[0027] Fifth, although the aluminum nitride layer can bring the above-mentioned excellent performance, the applicant found that if the non-magnetic phase aluminum nitride is excessive, the effective magnetic permeability of the magnetic core will decrease. Therefore, although its DC bias performance is slightly improved, its core loss will increase, and the hysteresis loss will increase. The hysteresis loss caused by excessive aluminum nitride coating is difficult to compensate for the reduced eddy current loss, so the weight of the aluminum nitride layer is controlled to 1-5wt% of the weight of the metal soft magnetic powder. Excessive silicone resin will bring the following disadvantages: the introduction of too much non-magnetic phase will cause the magnetic permeability of the magnetic powder core to drop sharply and the hysteresis loss to increase; in addition, excessive resin will directly cause the fluidity of the powder to deteriorate and affect the pressing formability.

[0028] In summary, the present application can obtain a metal soft magnetic composite material having high frequency, low loss and good heat resistance and heat dissipation performance at a relatively low cost through a simple operation process.

[0029] In a preferred embodiment, the aluminum nitride layer and the silicone resin layer are combined by a silane coupling agent. The silane coupling agent can further enhance the bonding force between the inorganic layer and the organic layer, which can not only further improve the temperature resistance and heat dissipation of the material, but also improve the magnetic ring strength of the composite material. Preferably, the silane coupling agent is selected from one or more of vinyl silane, alkyl silane or amino silane. Further preferably, the vinyl silane is selected from one or more of KH-151, KH-171, KH-172 or KH-188. Further preferably, the alkyl silane is selected from one or more of KH-2421, KH-481, KH-681 or KH-330. Further preferably, the amino silane is selected from one or more of KH-550, KH-902, KH-602 or KH-703. In order to further improve the bonding efficiency of the aluminum nitride layer and the silicone resin layer, the weight of the silane coupling agent is preferably 0.5 to 2 wt% of the weight of the metal soft magnetic powder.

[0030] In order to make the material have better loss performance, in a preferred embodiment, the metal soft magnetic powder is one or more of iron silicon powder, iron silicon aluminum powder or iron nickel molybdenum powder. Further preferably, by weight fraction, the composition of iron silicon powder includes 94.4-95.4wt% Fe, 4.5-5.5wt% Si and the balance of inevitable impurities; the composition of iron silicon aluminum powder includes 84.1-85.7wt% Fe, 9-10wt% Si, 5.2-5.8wt% Al and the balance of inevitable impurities; the composition of iron nickel molybdenum powder includes 17.8-19.9wt% Fe, 1.5-2.5wt% Mo, 78.5-79.6wt% Ni and the balance of inevitable impurities.

[0031] In order to further improve the insulating coating and bonding effect of the organic insulating coating layer, in a preferred embodiment, the material of the organic silicone resin layer is methyl phenyl silicone resin. Preferably, the methyl phenyl silicone resin is selected from one or more of KR-272, KR-311 or KR-282.

[0032] The present application also provides a method for preparing the aforementioned metal soft magnetic composite material, comprising the following steps: step S1, mixing metal soft magnetic powder and aluminum nitride powder and then ball milling to coat the outer surface of the metal soft magnetic powder with an aluminum nitride layer; step S2, mixing the metal soft magnetic powder coated with the aluminum nitride layer and a silicone resin and then granulating to coat the outer surface of the aluminum nitride layer with a silicone resin layer.

[0033] Based on the above reasons, the present application can obtain a metal soft magnetic composite material having high frequency, low loss and good heat resistance and heat dissipation performance at a relatively low cost and through a simple operation process.

[0034] In order to further improve the performance uniformity of the aluminum nitride layer, in a preferred embodiment, step S1 includes: S11, mixing anhydrous ethanol and metal soft magnetic powder (ultrasonic treatment time is not less than 10 minutes, and the ultrasonic frequency range is 20-40kHz), and then performing a first ball milling (ball milling time is 2-4 hours, and the ball-to-material ratio is 10-20:1) and a first drying (preferably the treatment temperature is 100-150°C) in sequence to obtain pretreated metal soft magnetic powder; S12, mixing the pretreated metal soft magnetic powder, aluminum nitride powder and anhydrous ethanol (ultrasonic treatment time is not less than 10 minutes, and the ultrasonic frequency range is 20-40kHz), and then performing a second ball milling (ball milling time is 12-48 hours, and the ball-to-material ratio is 10-20:1) and a second drying (preferably the treatment temperature is 100-150°C) in sequence to coat the outer surface of the metal soft magnetic powder with an aluminum nitride layer. In the second ball milling process, too short a ball milling time will result in aluminum nitride not being effectively coated on the surface of the magnetic powder, resulting in higher core loss and effective magnetic permeability and lower DC bias performance. However, too long a ball milling time will cause the magnetic powder particles to deform and cause a significant increase in hysteresis loss; in addition, too long a ball milling time means higher energy consumption and higher costs.

[0035] Considering that the particle size will affect the performance of the metal soft magnetic composite material, in order to obtain a magnetic powder core with low loss and high magnetic permeability, the present application further prefers a metal soft magnetic powder with a particle size of 200 to 800 meshes. In order to further improve the coating efficiency and coating uniformity of the aluminum nitride layer, in a preferred embodiment, the particle size of the aluminum nitride powder is 500 to 1000 meshes.

[0036] In order to further improve the synergistic effect of the aluminum nitride layer and the silicone resin layer, in a preferred embodiment, step S2 includes: S21, dissolving the silane coupling agent in anhydrous ethanol, and then adding the metal soft magnetic powder coated with the aluminum nitride layer to the system, and sequentially performing the first ultrasonic treatment (ultrasonic treatment time is not less than 10 minutes, and the ultrasonic frequency range is 20-40kHz), and the third drying (preferably the treatment temperature is 100-150°C) to obtain the surface-treated metal soft magnetic powder; S22, dissolving the silicone resin in acetone, and then adding the surface-treated metal soft magnetic powder to the system, and sequentially performing the second ultrasonic treatment (ultrasonic treatment time is not less than 10 minutes, and the ultrasonic frequency range is 20-40kHz), granulation (the mesh size of the sieve is 50-100 mesh), and drying (preferably the treatment temperature is 50-70°C) to obtain the metal soft magnetic composite material.

[0037] The present application also provides a magnetic powder core, which includes the aforementioned metal soft magnetic composite material and a release agent. Based on the above reasons, the magnetic powder core of the present application has both high frequency and low loss and good heat resistance and heat dissipation performance.

[0038] In an optional embodiment, the magnetic powder core is prepared by the following method: the aforementioned soft magnetic metal composite material is mixed with a release agent and then pressed to obtain a magnetic ring green body; the magnetic ring green body is then subjected to high temperature annealing in an inert atmosphere to obtain a magnetic powder core. Preferably, the amount of the release agent is 0.1 to 0.3% of the weight of the soft magnetic metal composite material; the pressing pressure is 125 to 145 kN; the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; the annealing temperature is 700 to 900°C, and the annealing time is 45 to 120 min.

[0039] The present application also provides an application of the aforementioned metal soft magnetic composite material in high-frequency electronic appliances. Based on the above reasons, the metal soft magnetic composite material of the present application has both high frequency low loss and good heat resistance and heat dissipation performance, which can better meet the needs of the high-frequency electronic appliance field.

[0040] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0041] Example 1

[0042] Select the FeSiAl metal powder (Fe content 85.5wt%, Si content 9.6wt%, Al content 4.9wt%) with the original powder size of 500 mesh. Mix the metal powder with anhydrous ethanol and place it in a ball mill to clean the impurities on the surface of the metal powder.

[0043] Aluminum nitride powder (1wt% of the sendust metal powder), anhydrous ethanol (8wt%) and the cleaned metal powder were mixed and placed in a ball mill (ball-to-material mass ratio of 20:1) for 8 hours. The milled metal powder was filtered and dried in an 80°C forced air drying oven.

[0044] The vinyl silane coupling agent KH-151 (the dosage is 0.2wt% of the sendust metal powder) is dissolved in ethanol (8wt%), and then the aluminum nitride-coated metal powder is added to the system, stirred and ultrasonically treated (frequency 25Hz) for 10min to allow the metal powder to react evenly and fully with the solution; and then dried completely in an 80°C forced air drying oven.

[0045] Methylphenyl silicone resin KR-272 (dosage is 1.5wt% of the sendust metal powder) is dissolved in acetone (10wt%), and then the metal powder treated with a coupling agent is added to the system, stirred and ultrasonically treated (frequency 25Hz) for 10 minutes to allow the metal powder to react evenly and fully with the solution to form an organic insulating layer, thereby obtaining a metal soft magnetic composite material.

[0046] The prepared metal soft magnetic composite material was sieved through a 60-mesh sieve to form particles and dried in a 60°C forced air drying oven; zinc stearate demolding powder was then added (the dosage was 0.5% of the weight of the metal soft magnetic composite material) and pressed under a pressure of 1500 kPa to form a magnetic powder core with OD = 12.75 mm and ID = 7.60 mm. The pressed magnetic powder core was placed in a nitrogen atmosphere at 650°C for heat treatment for 60 minutes, and then the soft magnetic properties were tested.

[0047] The weight of the aluminum nitride layer is 1 wt% of the weight of the metal soft magnetic powder; the weight of the silicone resin layer is 1.5 wt% of the weight of the metal soft magnetic powder.

[0048] Example 2

[0049] The only difference from Example 1 is that the weight of the aluminum nitride layer is 2 wt % of the weight of the metal soft magnetic powder.

[0050] Example 3

[0051] The only difference from Example 1 is that the weight of the aluminum nitride layer is 3 wt % of the weight of the metal soft magnetic powder.

[0052] Example 4

[0053] The only difference from Example 1 is that the aluminum nitride powder, anhydrous ethanol and the cleaned metal powder are mixed and then placed in a ball mill for 4 hours.

[0054] Example 5

[0055] The only difference from Example 1 is that the aluminum nitride powder, anhydrous ethanol and the cleaned metal powder are mixed and then placed in a ball mill for 12 hours.

[0056] Example 6

[0057] The only difference from Example 1 is that the aluminum nitride powder, anhydrous ethanol and the cleaned metal powder are mixed and then placed in a ball mill for 24 hours.

[0058] Example 7

[0059] The only difference from Example 1 is that the aluminum nitride powder, anhydrous ethanol and the cleaned metal powder are mixed and then placed in a ball mill for 50 hours.

[0060] Comparative Example 1

[0061] The only difference from Example 1 is that no aluminum nitride layer is provided.

[0062] Comparative Example 2

[0063] The only difference from Example 1 is that the weight of the aluminum nitride layer is 6 wt % of the weight of the metal soft magnetic powder.

[0064] Comparative Example 3

[0065] The only difference from Example 1 is that the weight of the organic silicone resin layer is 5 wt % of the weight of the metal soft magnetic powder.

[0066] Test Method

[0067] Under the test conditions of 100-1000kHz, 50mT, 298.15K and 373.15K, the losses of the magnetic powder cores provided by the embodiments and the comparative examples were compared.

[0068] Table 1

[0069]

[0070] By comparing Examples 1-6 with Comparative Example 1, it can be seen that under high temperature conditions, the loss increase of the magnetic core with an aluminum nitride coating is significantly smaller than that without an aluminum nitride coating, indicating that the heat resistance of the magnetic core with an aluminum nitride coating is better than that without an aluminum nitride coating. Figure 1 The loss test diagrams of comparative example 1 and embodiment 1 of the present invention at different frequencies are shown. By comparing embodiment 1 with comparative example 1, it can be seen that the magnetic powder core without inorganic coating with aluminum nitride has higher effective magnetic permeability, higher core loss and lower DC bias performance. This shows that the inorganic coating layer of aluminum nitride can effectively play an insulating role, thereby greatly reducing the eddy current loss between the magnetic powder particles. In addition, aluminum nitride has a high thermal conductivity (about 320w / mk) and can withstand high temperatures of 1400°C. Therefore, the use of aluminum nitride as an inorganic layer can greatly increase the heat resistance and heat dissipation capacity of the magnetic powder core, which can meet the future needs of the field of high-frequency electronic appliances.

[0071] From the comparison between Examples 1-3 and Comparative Example 2, it can be seen that although the aluminum nitride layer can bring the above-mentioned excellent performance, if the non-magnetic aluminum nitride is excessive, the effective magnetic permeability of the magnetic core will decrease. Therefore, although its DC bias performance is slightly improved, its core loss increases, and it will also cause an increase in hysteresis loss. The hysteresis loss caused by excessive aluminum nitride coating is difficult to compensate for the reduced eddy current loss.

[0072] From the comparison between Examples 1-3 and Comparative Example 3, it can be seen that excessive silicone resin will bring the following disadvantages: reduced magnetic permeability and increased losses; in addition, during the pressing process, due to excessive resin, the powder fluidity becomes poor, which greatly increases the difficulty of pressing and molding.

[0073] From the comparison between Examples 1, 5, 6 and Examples 4, 7, it can be seen that too short a ball milling time will result in the aluminum nitride being unable to be effectively coated on the surface of the magnetic powder, resulting in higher core loss and effective magnetic permeability and lower DC bias performance. However, too long a ball milling time will result in deformation of the magnetic powder particles and greatly increase the hysteresis loss; in addition, too long a ball milling time means higher energy consumption and higher cost.

[0074] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A metal soft magnetic composite material, characterized in that: The metal soft magnetic composite material includes metal soft magnetic powder and an aluminum nitride layer and a silicone resin layer sequentially coated on the outer surface of the metal soft magnetic powder; the weight of the aluminum nitride layer is 1-5wt% of the weight of the metal soft magnetic powder; the weight of the silicone resin layer is 0.8-4wt% of the weight of the metal soft magnetic powder.

2. The metal soft magnetic composite material according to claim 1, characterized in that: The aluminum nitride layer and the organic silicone resin layer are combined by a silane coupling agent; Preferably, the silane coupling agent is selected from one or more of vinyl silane, alkyl silane or amino silane; Further preferably, the vinyl silane is selected from one or more of KH-151, KH-171, KH-172 or KH-188; Further preferably, the alkylsilane is selected from one or more of KH-2421, KH-481, KH-681 or KH-330; Further preferably, the aminosilane is selected from one or more of KH-550, KH-902, KH-602 or KH-703.

3. The metal soft magnetic composite material according to claim 1 or 2, characterized in that: The metal soft magnetic powder is one or more of iron silicon powder, iron silicon aluminum powder or iron nickel molybdenum powder; Further preferably, the iron silicon powder comprises, by weight percentage, 94.4-95.4wt% of Fe, 4.5-5.5wt% of Si and the remainder of inevitable impurities; Further preferably, the composition of the sendust powder includes, by weight percentage, 84.1-85.7 wt % of Fe, 9-10 wt % of Si, 5.2-5.8 wt % of Al and the remainder of inevitable impurities; Further preferably, the iron-nickel-molybdenum powder comprises, by weight percentage, 17.8-19.9wt% of Fe, 1.5-2.5wt% of Mo, 78.5-79.6wt% of Ni and the remainder of inevitable impurities.

4. The metal soft magnetic composite material according to any one of claims 1 to 3, characterized in that: The material of the organic silicone resin layer is methyl phenyl silicone resin; Preferably, the methylphenyl silicone resin is selected from one or more of KR-272, KR-311 or KR-282.

5. The metal soft magnetic composite material according to claim 2, characterized in that: The weight of the silane coupling agent is 0.5-2 wt % of the weight of the metal soft magnetic powder.

6. A method for preparing a metal soft magnetic composite material, characterized in that: The following steps are involved: Step S1, mixing a metal soft magnetic powder and an aluminum nitride powder and then ball milling the mixture to coat an aluminum nitride layer on the outer surface of the metal soft magnetic powder; Step S2, mixing the metal soft magnetic powder coated with the aluminum nitride layer and an organic silicone resin and then granulating them to coat the outer surface of the aluminum nitride layer with an organic silicone resin layer.

7. The method for preparing the metal soft magnetic composite material according to claim 6, characterized in that: The step S1 comprises: S11, mixing anhydrous ethanol with the metal soft magnetic powder and then sequentially performing a first ball milling and a first drying to obtain a pretreated metal soft magnetic powder; S12, mixing the pretreated metal soft magnetic powder, the aluminum nitride powder and anhydrous ethanol, and then sequentially performing a second ball milling and a second drying to coat the outer surface of the metal soft magnetic powder with an aluminum nitride layer; Preferably, the particle size of the metal soft magnetic powder is 200-800 mesh; Preferably, the particle size of the aluminum nitride powder is 500-1000 mesh; Preferably, the first ball milling process is performed for 2 to 4 hours, and the ball-to-material ratio is 10 to 20:1; Preferably, the processing time of the second ball milling is 12 to 48 hours, and the ball-to-material ratio is 10 to 20:

1.

8. The method for preparing the metal soft magnetic composite material according to claim 6 or 7, characterized in that: The step S2 comprises: S21, dissolving a silane coupling agent in anhydrous ethanol, and then adding the metal soft magnetic powder coated with the aluminum nitride layer into the system, and sequentially performing a first ultrasonic treatment and a third drying to obtain a surface-treated metal soft magnetic powder; S22, dissolving the organic silicone resin in acetone, and then adding the surface treated metal soft magnetic powder into the system, and performing second ultrasonication, granulation, and drying in sequence to obtain the metal soft magnetic composite material.

9. A magnetic powder core, characterized in that: The magnetic powder core comprises the metal soft magnetic composite material according to any one of claims 1 to 5 and a release agent.

10. Use of the metal soft magnetic composite material according to any one of claims 1 to 5 in high-frequency electronic appliances.

Citation Information

Patent Citations

  • Preparation method of MnO-SiO2 insulation coated metal soft magnetic powder core

    CN114512323A